Correlation of Lip Shape and Type of Smile in The Perception of Aesthetics in Patients Between18-30 Years - A Photographic Study - HARIHARANA, SHA.S.; R, SUBHASHREE; V, RAKSHAGAN (The journal of contemporary issues in business and government, 2021)
Smile is characterised by upward curving of the corners of the mouth, indicates pleasure and plays an important role in social interactions. The study was done to assess the relation between the shape of lips, type of smile and their effect in the perception of aesthetic between the age group of 18-30 years.The study was designed to be a photographic analysis of smiles of 70 subjects between 18-30 years. The study was done in Saveetha Dental College, Chennai, India during the time frame of March-April 2020. The study analysed the type of smile, the shape of the lips and the smile line and its influence on the smile esthetics. An esthetic score was given to the patient on a score from 1-5, five being excellent and 1 being poor. These results were correlated to understand their influence on each other. Descriptive statistics was used to measure frequency and Pearson’s correlation was performed to analyse the correlation. Moderately arched lips(53%), medium smile line(66.7%) and both Cuspid and commissural type(40%) of smile showed association with the highest grade of smile esthetics. There is a negligible correlation between smile line and esthetic score, low positive correlation of type of smile with the perceived esthetics, and negative correlation between shape of smile and esthetics (-0.22). The esthetics of smile depends on the peri oral structures as much as it depends on the teeth and associated structures.Development of an index to incorporate the aspects of lips and face in the quantification of esthetic score would best enable to obtain a wholesome picture and also allows standardised comparisons. Further research is encouraged.